Grinding aid as well as preparation method and application thereof
By combining specific surfactants with a to-treated solution containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate into a grinding aid, the problem of poor adaptability and stability of traditional grinding aid is solved, efficient grinding of powder coatings is achieved, and the dispersion and fluidity of the materials are improved, and the economic and environmental benefits are good.
Patent Information
- Application Number
- CN202510083563.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Traditional agitators have poor adaptability and stability in powder coating grinding, low grinding efficiency, and cannot meet the increasing requirements for powder coating materials.
A specific surfactant is used to combine with a to-treated solution containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate into a grinding aid to improve the interface wetting performance of the material, weaken the powder aggregation phenomenon, reduce surface energy, and thus improve the dispersion, grading and fluidity of the material.
It significantly improves the dispersion, interface wetting, emulsification and stability of the grinding materials, reduces the grinding energy consumption, improves grinding efficiency, and is cheap, with good economic and environmental benefits.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wastewater resource utilization, and in particular to a grinding aid and a preparation method and application thereof. Background Art
[0002] Calcium carbonate is the most common filler in powder coatings. In recent years, with the ultra-fineness, structural complexity and surface modification technology of calcium carbonate, calcium carbonate products have tended to be specialized, refined and functionalized, and their particle size requirements have become higher and higher with the improvement of technology. During the crushing process, calcium carbonate stone will go through a cycle of crack formation, crack expansion, crack fracture and then crack formation. When the molecular force increases to a certain extent, the material begins to agglomerate until a dynamic balance between crushing and agglomeration is reached, and the particle size of the material no longer changes. Without changing the grinding equipment and its production process, adding a suitable grinding aid is one of the effective ways to break the dynamic balance between crushing and agglomeration.
[0003] Traditional grinding aids mainly include inorganic grinding aids (sodium hexametaphosphate and sodium tripolyphosphate, etc.), organic grinding aids (ethylene glycol and triethanolamine, etc.) and polymer grinding aids (polycarboxylates and polyacrylic acid derivatives, etc.). Traditional grinding aids have poor adaptability and stability, low grinding efficiency, and the particle grading and fluidity of the grinding materials cannot meet the increasingly high requirements for powder coating materials. Summary of the invention
[0004] Based on this, it is necessary to provide a grinding aid that can improve the particle grading and fluidity of the material, and a preparation method and application thereof.
[0005] In one aspect of the present application, a grinding aid is provided, which includes a solution to be treated and a surfactant; the solution to be treated contains sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate; the surfactant includes at least one of sodium dodecylbenzene sulfonate, sodium lignin sulfonate, allyl polyether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether.
[0006] The present application compounds a specific surfactant with a solution to be treated containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate into a grinding aid. The specific surfactant and the solution to be treated containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate cooperate with each other to synergistically enhance the effect, which can greatly improve the interfacial wetting performance of the material, weaken the agglomeration of powders, reduce surface energy, and thus improve the dispersibility of the material, and improve the gradation and fluidity of the material. The sodium acrylate in the solution to be treated can promote the dissolution or conversion of the grinding material; the sodium p-toluenesulfonate in the solution to be treated not only has good surface activity, but can also be adsorbed on the surface of the grinding material particles, and use electrostatic repulsion to maintain the dispersibility and stability of the grinding slurry; the sodium hydroxide in the solution to be treated can be used as a pH regulator to change the charge properties and quantity of the particle surface and improve the dispersibility of the particles; the solution to be treated compounded with a specific surfactant as a grinding aid greatly improves the dispersibility, interfacial wettability, emulsification and stability of the grinding material.
[0007] Sodium dodecylbenzene sulfonate has a regular structure, strong dispersibility and surface activity, can effectively prevent particle agglomeration, and is less affected by external interference factors; sodium lignin sulfonate has good dispersibility and is not easy to agglomerate; the sulfonic acid group in the structure of sodium dodecylbenzene sulfonate or sodium lignin sulfonate will ionize in aqueous solution, so that the surface of the particles have the same charge and repel each other. When the particles are subjected to grinding force, cracks will appear. Sodium dodecylbenzene sulfonate or sodium lignin sulfonate cooperates with sodium acrylate and sodium toluene sulfonate in the solution to be treated, which can not only accelerate the generation of cracks, but also prevent the healing of cracks, reduce powder agglomeration, and improve the grinding effect.
[0008] The molecular chain structure of allyl polyether gives it good dispersibility and large steric hindrance, providing a large number of reactive sites. It cooperates with sodium acrylate, sodium toluenesulfonate and sodium hydroxide in the solution to be treated to produce polymerization, cross-linking and other reactions, which is beneficial to improve the overall strength and stability of the grinding slurry and reduce agglomeration.
[0009] When fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether are used in combination with sodium acrylate, sodium toluenesulfonate and sodium hydroxide in the solution to be treated as grinding slurry, they all show excellent wettability, emulsification and dispersibility. During grinding, they can reduce the surface tension between the particles and the slurry, so that the particles can be better dispersed in the slurry and prevent the particles from agglomerating.
[0010] The above-mentioned grinding aids can reduce the viscosity of wet-grinded materials, avoid stratification of materials, and thus improve the stability of materials.
[0011] After the grinding aid is used, the aggregated particles in the material are reduced, the friction between the particles becomes smaller, the stacking is more compact, the comprehensive properties such as oil absorption and activation are better, and the performance is long-lasting.
[0012] The above-mentioned grinding aid improves the material grinding efficiency, reduces the grinding energy consumption, is low in cost, and has good economic and environmental benefits.
[0013] In some embodiments, the mass ratio of the solution to be treated to the surfactant is 1:0.08-0.39.
[0014] In some embodiments, the grinding aid satisfies at least one of the following conditions:
[0015] (1) The surfactant includes sodium dodecylbenzene sulfonate and allyl polyether;
[0016] (2) The surfactant includes the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether.
[0017] In some embodiments, the grinding aid satisfies at least one of the following conditions:
[0018] (1) The mass ratio of the solution to be treated, the sodium dodecylbenzene sulfonate and the allyl polyether is 1:0.1-0.32:0.04-0.1;
[0019] (2) The mass ratio of the solution to be treated, the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether is 1:0.12-0.33:0.025-0.08.
[0020] In some embodiments, the solution to be treated is wastewater from the production of acrylic acid and its esters, the solid content of the wastewater from the production of acrylic acid and its esters is 30% to 50%, the mass content of sodium acrylate in the wastewater from the production of acrylic acid and its esters is 15% to 37%, the mass content of sodium hydroxide in the wastewater from the production of acrylic acid and its esters is 0.3% to 13%, and the mass content of sodium p-toluenesulfonate in the wastewater from the production of acrylic acid and its esters is 0.3% to 5%.
[0021] The second aspect of the present application provides a method for preparing the grinding aid as described in the first aspect, comprising the following steps: blending the solution to be treated and the surfactant to prepare the grinding aid.
[0022] In some embodiments, the method for preparing the grinding aid satisfies at least one of the following conditions:
[0023] (1) The solution to be treated is wastewater produced by the production of acrylic acid and its esters, and before the blending, it also includes a concentration step: based on the mass content, the wastewater produced by the production of acrylic acid and its esters with a solid content of 2% to 20% is concentrated into the wastewater produced by the production of acrylic acid and its esters with a solid content of 30% to 50%;
[0024] (2) The blending temperature of the blending is 40°C to 50°C.
[0025] The third aspect of the present application provides a use of the grinding aid as described in the first aspect in a grinding process.
[0026] In some embodiments, the use of the grinding aid in the grinding process comprises the following steps:
[0027] The calcium carbonate coarse powder is wet-ground with the grinding aid and water to prepare calcium carbonate slurry.
[0028] In some embodiments, the use of the grinding aid in the grinding process satisfies at least one of the following conditions:
[0029] (1) The amount of the grinding aid added is 0.2% to 0.5% of the mass of the calcium carbonate coarse powder;
[0030] (2) The average particle size of the calcium carbonate coarse powder is 250 mesh to 500 mesh;
[0031] (3) The grinding time of the wet grinding is 25min~45min. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant embodiments, wherein preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0034] Fillers in powder coatings can not only reduce costs, but also improve material properties. In powder coatings, calcium carbonate is one of the most common fillers. In recent years, with the development of ultrafine calcium carbonate, complex structure and surface modification technology, calcium carbonate filler products tend to be specialized, refined and functionalized, and the corresponding particle size requirements are getting higher and higher. Therefore, technicians try to add grinding aids in the grinding process to solve this problem, but traditional grinding aids have poor adaptability and stability, low grinding efficiency, and the particle grading and fluidity of the ground material cannot meet the increasing requirements for powder coating materials. Based on this, one aspect of the present application provides a grinding aid, the grinding aid includes a solution to be treated and a surfactant; the solution to be treated contains sodium acrylate, sodium hydroxide and sodium p-toluene sulfonate; the surfactant includes at least one of sodium dodecylbenzene sulfonate, sodium lignin sulfonate, allyl polyether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether.
[0035] The present application compounds a specific surfactant with a solution to be treated containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate into a grinding aid. The specific surfactant and the solution to be treated containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate cooperate with each other to synergistically enhance the effect, which can greatly improve the interfacial wetting performance of the material, weaken the agglomeration of powders, reduce surface energy, and thus improve the dispersibility of the material, and improve the gradation and fluidity of the material. The sodium acrylate in the solution to be treated can promote the dissolution or conversion of the grinding material; the sodium p-toluenesulfonate in the solution to be treated not only has good surface activity, but can also be adsorbed on the surface of the grinding material particles, and use electrostatic repulsion to maintain the dispersibility and stability of the grinding slurry; the sodium hydroxide in the solution to be treated can be used as a pH regulator to change the charge properties and quantity of the particle surface and improve the dispersibility of the particles; the solution to be treated compounded with a specific surfactant as a grinding aid greatly improves the dispersibility, interfacial wettability, emulsification and stability of the grinding material.
[0036] Sodium dodecylbenzene sulfonate has a regular structure, strong dispersibility and surface activity, can effectively prevent particle agglomeration, and is less affected by external interference factors; sodium lignin sulfonate has good dispersibility and is not easy to agglomerate; the sulfonic acid group in the structure of sodium dodecylbenzene sulfonate or sodium lignin sulfonate will ionize in aqueous solution, so that the surface of the particles have the same charge and repel each other. When the particles are subjected to grinding force, cracks will appear. Sodium dodecylbenzene sulfonate or sodium lignin sulfonate cooperates with sodium acrylate and sodium toluene sulfonate in the solution to be treated, which can not only accelerate the generation of cracks, but also prevent the healing of cracks, reduce powder agglomeration, and improve the grinding effect.
[0037] The molecular chain structure of allyl polyether gives it good dispersibility and large steric hindrance, providing a large number of reactive sites. It cooperates with sodium acrylate, sodium toluenesulfonate and sodium hydroxide in the solution to be treated to produce polymerization, cross-linking and other reactions, which is beneficial to improve the overall strength and stability of the grinding slurry and reduce agglomeration.
[0038] When fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether are used in combination with sodium acrylate, sodium toluenesulfonate and sodium hydroxide in the solution to be treated as grinding slurry, they all show excellent wettability, emulsification and dispersibility. During grinding, they can reduce the surface tension between the particles and the slurry, so that the particles can be better dispersed in the slurry and prevent the particles from agglomerating.
[0039] The above-mentioned grinding aids can reduce the viscosity of wet-grinded materials, avoid stratification of materials, and thus improve the stability of materials.
[0040] After the grinding aid is used, the aggregated particles in the material are reduced, the friction between the particles becomes smaller, the stacking is more compact, the comprehensive properties such as oil absorption and activation are better, and the performance is long-lasting.
[0041] The above-mentioned grinding aid improves the material grinding efficiency, reduces the grinding energy consumption, is low in cost, and has good economic and environmental benefits.
[0042] It can be understood that the solution to be treated can be a mixed solution containing three components: sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate.
[0043] In some embodiments, the solution to be treated is saline wastewater containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate.
[0044] In some embodiments, the solution to be treated is a mixture of three types of wastewater: wastewater containing sodium acrylate, wastewater containing sodium hydroxide, and saline wastewater containing sodium toluenesulfonate.
[0045] In some embodiments, the solution to be treated is a mixed solution obtained by dissolving sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate in water.
[0046] Furthermore, in the solution to be treated, the solid content is 30% to 50%, the mass content of sodium acrylate is 15% to 37%, the mass content of sodium hydroxide is 0.3% to 13%, and the mass content of sodium p-toluenesulfonate is 0.3% to 5%.
[0047] In some embodiments, the solution to be treated is wastewater from the production of acrylic acid and its esters. In the present application, a specific surfactant is compounded with wastewater from the production of acrylic acid and its esters containing sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate to form a grinding aid, which can not only serve as a grinding aid to improve the dispersibility of the material to be ground, improve the gradation and fluidity of the material, but also realize the resource utilization of wastewater, reduce pollution, and bring environmental benefits.
[0048] It is understood that when acrylic acid and alcohols are used to produce acrylic acid and its esters by esterification, in order to ensure the selectivity and conversion rate of the reaction, a slight excess of acrylic acid is generally involved in the reaction. Therefore, at the end of the reaction, low-concentration alkaline water is required to clean the reaction device to prevent excessive acrylic acid from entering the separation section and corroding the equipment. However, the cleaning process will produce a large amount of salt-containing alkaline washing wastewater, which contains a lot of sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate (residual catalyst). Among them, acrylic acid and its esters are a general term for esters of acrylic acid and its homologues, including methyl acrylate, ethyl acrylate, methyl 2-methacrylate and ethyl 2-methacrylate. According to actual conditions, the components of the alkaline washing wastewater can be concentrated to the required mass content through triple-effect evaporation and concentration treatment, so as to obtain the above-mentioned acrylic acid and its ester production wastewater. In addition, the unconcentrated alkaline washing wastewater is also applicable to this application.
[0049] In some embodiments, the solution to be treated is wastewater from the production of acrylic acid and its esters, and the wastewater from the production of acrylic acid and its esters contains sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate; the solid content of the wastewater from the production of acrylic acid and its esters is 30% to 50%, the mass content of sodium acrylate in the wastewater from the production of acrylic acid and its esters is 15% to 37%, the mass content of sodium hydroxide in the wastewater from the production of acrylic acid and its esters is 0.3% to 13%, and the mass content of sodium p-toluenesulfonate in the wastewater from the production of acrylic acid and its esters is 0.3% to 5%.
[0050] In some embodiments, the mass ratio of the solution to be treated to the surfactant is 1:0.08-0.39.
[0051] As an example, the mass ratio of the solution to be treated to the surfactant can be 1:0.08, 1:0.09, 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19, 1:0.20, 1:0.21, 1:0.22, 1:0. 23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29, 1:0.30, 1:0.31, 1:0.32, 1:0.33, 1:0.34, 1:0.35, 1:0.36, 1:0.37, 1:0.38 and 1:0.39, or any two of the above points can be used as end values. The mass ratio of the solution to be treated and the surfactant can further optimize the gradation of the ground material, reduce the D50 of the material, increase the particle size below 2μm, and improve the fluidity, stability, oil absorption and activation of the material.
[0052] The mass ratio of the solution to be treated to the surfactant is preferably 1:0.2-0.35.
[0053] In some embodiments, the surfactant includes the sodium dodecylbenzene sulfonate and the allyl polyether.
[0054] In some embodiments, the grinding aid includes a solution to be treated, the sodium dodecylbenzene sulfonate and the allyl polyether.
[0055] In some embodiments, the grinding aid comprises a solution to be treated, sodium dodecylbenzene sulfonate and allyl polyether; the mass ratio of the solution to be treated, sodium dodecylbenzene sulfonate and allyl polyether is 1:0.1-0.32:0.04-0.1. The mass ratio of the solution to be treated, sodium dodecylbenzene sulfonate and allyl polyether is preferably 1:0.15-0.3:0.05-0.1. The mass ratio of the solution to be treated, sodium dodecylbenzene sulfonate and allyl polyether is more preferably 1:0.15-0.25:0.06-0.08.
[0056] The grinding aid is a synergistic combination of the solution to be treated, sodium dodecylbenzene sulfonate and the allyl polyether, optimizes the gradation of the ground material, reduces the D50 of the material, increases the number of particles with a diameter below 2 μm, and improves the fluidity, stability, oil absorption and activation of the material.
[0057] Furthermore, the solution to be treated adopts wastewater produced by acrylic acid and its esters.
[0058] In some embodiments, the surfactant includes the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether.
[0059] In some embodiments, the grinding aid comprises a solution to be treated, the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether.
[0060] In some embodiments, the grinding aid includes the solution to be treated, the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether; the mass ratio of the acrylic acid and its ester production wastewater, the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether is 1:0.12~0.33:0.025~0.08.
[0061] The grinding aid optimizes the grading of the grinding material, reduces the D50 of the material, increases the particle size below 2 μm, and improves the fluidity, stability, oil absorption and activation of the material through the interaction of the solution to be treated, sodium lignin sulfonate and alkylphenol polyoxyethylene ether.
[0062] Furthermore, the solution to be treated adopts wastewater produced by acrylic acid and its esters.
[0063] In some embodiments, the grinding aid includes a solution to be treated and sodium dodecylbenzene sulfonate.
[0064] In some embodiments, the grinding aid includes a solution to be treated and sodium lignin sulfonate.
[0065] In some embodiments, the grinding aid includes a solution to be treated and allyl polyether.
[0066] In some embodiments, the grinding aid includes a solution to be treated and fatty alcohol polyoxyethylene ether.
[0067] In some embodiments, the grinding aid includes a solution to be treated and alkylphenol polyoxyethylene ether.
[0068] In some embodiments, the grinding aid includes a solution to be treated and nonylphenol polyoxyethylene ether.
[0069] In some embodiments, the grinding aid includes a solution to be treated, sodium dodecylbenzene sulfonate and sodium lignin sulfonate.
[0070] In some embodiments, the grinding aid includes a solution to be treated, sodium dodecylbenzene sulfonate and fatty alcohol polyoxyethylene ether.
[0071] In some embodiments, the grinding aid includes a solution to be treated, sodium dodecylbenzene sulfonate and alkylphenol polyoxyethylene ether.
[0072] In some embodiments, the grinding aid includes a solution to be treated, sodium dodecylbenzene sulfonate and nonylphenol polyoxyethylene ether.
[0073] In some embodiments, the grinding aid includes a solution to be treated, sodium lignin sulfonate and allyl polyether.
[0074] In some embodiments, the grinding aid includes a solution to be treated, sodium lignin sulfonate and fatty alcohol polyoxyethylene ether.
[0075] In some embodiments, the grinding aid includes a solution to be treated, sodium lignin sulfonate and nonylphenol polyoxyethylene ether.
[0076] In some embodiments, the molecular weight of the allyl polyether is 1000 to 2400. The molecular weight of the allyl polyether is preferably 1000 to 2000.
[0077] The second aspect of the present application provides a method for preparing the grinding aid described in the first aspect, comprising the following steps: blending the solution to be treated and the surfactant to prepare the grinding aid.
[0078] In some embodiments, the blending temperature of the blending is 40°C to 50°C.
[0079] In some of the embodiments, the solution to be treated adopts wastewater from the production of acrylic acid and its esters, and before the blending, it also includes a concentration step: based on the mass content, the wastewater from the production of acrylic acid and its esters with a solid content of 2% to 20% is concentrated into the wastewater from the production of acrylic acid and its esters with a solid content of 30% to 50%.
[0080] In some embodiments, in the acrylic acid and ester production wastewater with a solid content of 2% to 20%, the mass content of sodium acrylate is 0.5% to 20%, the mass content of sodium hydroxide is 0.1% to 5%, and the mass content of sodium p-toluenesulfonate is 0.1% to 2%. At present, the composition and mass ratio of the alkaline washing wastewater generated by washing the production equipment with sodium hydroxide in the production process of acrylic acid and ester are usually within this range. The grinding aid prepared by concentrating the alkaline washing wastewater has higher grinding efficiency and better effect.
[0081] In some embodiments, the concentration step is performed by triple-effect evaporation, which can concentrate the solution and recover the solvent.
[0082] In some of the embodiments, the triple-effect evaporation concentration treatment is to evaporate and concentrate acrylic acid and its ester production wastewater with a solid content of 2% to 20% through three separators, namely a first-effect separator, a second-effect separator and a third-effect separator, to finally obtain the desired acrylic acid and its ester production wastewater with a solid content of 30% to 50%.
[0083] In some embodiments, the gas phase temperature of the first-effect separator is 70.5°C ~81.5°C, and the gas phase pressure is -30.3 kpa ~40.3 kpa.
[0084] In some embodiments, the gas phase temperature of the second-effect separator is 60.8°C ~70.5°C, and the gas phase pressure is -55.7 kpa ~64.7 kpa.
[0085] In some of the embodiments, the gas phase temperature of the triple-effect separator is 50.5°C to 60.5°C, and the gas phase pressure is -65.6 kpa to 73.6 kpa.
[0086] Furthermore, the first-effect separator, the second-effect separator and the third-effect separator adopt evaporators.
[0087] The third aspect of the present application provides a use of the grinding aid as described in the first aspect in a calcium carbonate grinding process.
[0088] When the aforementioned grinding aids are applied in the grinding process, the deep utilization of wastewater from the production of acrylic acid and its esters is achieved, which can improve the particle size distribution and rheology of the ground materials, enhance the comprehensive effects such as the activity rate and stability of the materials, and also reduce the energy consumption of grinding.
[0089] In some embodiments, the application comprises the following steps:
[0090] The calcium carbonate coarse powder is wet-ground with the grinding aid and water to prepare calcium carbonate slurry.
[0091] When the aforementioned grinding aids are applied in the calcium carbonate grinding process, the deep utilization of the wastewater produced by acrylic acid and its esters is achieved, and it has the comprehensive effects of reducing the viscosity of the calcium carbonate slurry, improving the grading and rheological properties of calcium carbonate particles, and increasing the activity rate and stability of calcium carbonate, and also reduces the energy consumption of grinding.
[0092] In some embodiments, the average particle size of the calcium carbonate coarse powder is 250 mesh to 500 mesh.
[0093] In some embodiments, the wet grinding time is 25 min to 45 min.
[0094] In some embodiments, the use of the grinding aid in the calcium carbonate grinding process includes: crushing the dried calcite ore with a jaw crusher, and then dry grinding it with a ball mill to obtain a coarse calcium carbonate powder; then uniformly mixing the coarse calcium carbonate powder, the grinding aid and water, and feeding it into a ball mill for wet grinding, the grinding time is 25 min ~ 45 min, to obtain a calcium carbonate slurry.
[0095] Furthermore, the calcium carbonate content in the calcite ore is ≥95%; the average particle size of the calcite ore is 12 mm ~25 mm; the average particle size of the calcite ore after jaw crushing is 45 mesh ~65 mesh; the average particle size of the calcium carbonate coarse powder is 250 mesh ~500 mesh.
[0096] In some embodiments, the grinding aid is added in an amount of 0.2% to 0.5% by mass of the calcium carbonate coarse powder.
[0097] In some embodiments, the grinding aid is added by spraying, so that the grinding aid is more fully dispersed in the calcium carbonate powder.
[0098] In some embodiments, the wastewater from the production of acrylic acid and its esters is alkaline washing wastewater generated by washing the production equipment with sodium hydroxide during the production process of ethyl acrylate, propyl acrylate or butyl acrylate.
[0099] The following are specific embodiments.
[0100] Take the alkali washing wastewater generated by washing the ethyl acrylate production unit with sodium hydroxide in the ethyl acrylate production process (esterification of acrylic acid and ethanol to produce ethyl acrylate). The components in the alkali washing wastewater are as follows: sodium acrylate, sodium p-toluenesulfonate, sodium hydroxide, alcohols, aldehydes, sodium sulfate, sodium chloride, and water-insoluble calcium salts, magnesium salts and inevitable solid impurities; the solid content of the alkali washing wastewater is 2%~20%, the mass content of sodium acrylate is 0.5%~20%, the mass content of sodium hydroxide is 0.1%~5%, and the mass content of sodium p-toluenesulfonate is 0.1%~2%. Specifically, due to the reaction conditions and reaction raw materials, the ethyl acrylate production unit may have residual raw materials: acrylic acid, catalyst sodium p-toluenesulfonate and ethanol; may have residual organic by-products: formaldehyde and acrolein; may have residual sodium sulfate, sodium chloride, and water-insoluble calcium salts, magnesium salts and other inevitable solid impurities in the raw materials; and may also have residual product ethyl acrylate. After the ethyl acrylate production unit is cleaned with sodium hydroxide, acrylic acid reacts to form sodium acrylate; ethyl acrylate will be hydrolyzed into sodium acrylate and the corresponding small molecule alcohol. Therefore, the components in the alkaline washing wastewater are sodium acrylate, sodium p-toluenesulfonate, sodium hydroxide, alcohols, aldehydes, sodium sulfate, sodium chloride, and water-insoluble calcium salts, magnesium salts and inevitable solid impurities;
[0101] Then the alkali-washing wastewater is filtered and pre-treated to remove water-insoluble calcium salts, magnesium salts and inevitable solid impurities;
[0102] Then, a triple-effect evaporation concentration treatment is performed to remove alcohols, aldehydes, sodium sulfate and sodium chloride in the alkali washing wastewater, and a concentration treatment is performed to obtain the desired acrylic acid and its ester production wastewater. The acrylic acid and its ester production wastewater contains only three components: sodium acrylate, sodium hydroxide and sodium p-toluenesulfonate. The solid content of the acrylic acid and its ester production wastewater is 30% to 50%, the mass content of sodium acrylate is 15% to 37%, the mass content of sodium hydroxide is 0.3% to 13%, and the mass content of sodium p-toluenesulfonate is 0.3% to 5%.
[0103] Among them, the specific steps in the three-effect evaporation concentration process are as follows:
[0104] The alkali washing wastewater is subjected to a first-effect separation treatment in a first-effect separator, the gas phase temperature of the first-effect separator is 70.5~81.5°C, and the gas phase pressure is -30.3~40.3kpa, so that alcohols and aldehydes are volatilized; a second-effect separation treatment is carried out in a second-effect separator, the gas phase temperature of the second-effect separator is 60.8~70.5°C, and the gas phase pressure is -55.7~64.7kpa, so that sodium sulfate is partially crystallized; a third-effect separation treatment is carried out in a third-effect separator, the gas phase temperature of the third-effect separator is 50.5~60.5°C, and the gas phase pressure is -65.6~73.6kpa, so that sodium sulfate and sodium chloride are crystallized and precipitated, and the wastewater is concentrated to the required solid content after filtration.
[0105] The specific contents of the components in the wastewater produced by the production of acrylic acid and its esters are as described in the examples.
[0106] Example 1
[0107] 300 g of wastewater from the production of acrylic acid and its esters, 75 g of sodium dodecylbenzene sulfonate and 18 g of allyl polyether with a molecular weight of 2000 were stirred in a water bath at 45° C. for 1 hour to prepare a grinding aid.
[0108] Among them, the solid content of the above-mentioned acrylic acid and its ester production wastewater is 49.73%, the mass content of sodium acrylate is 36.79%, the mass content of sodium hydroxide is 8.06%, and the mass content of sodium p-toluenesulfonate is 4.88%; the model of sodium dodecylbenzenesulfonate is LAS-30; and the model of allyl polyether is APEG-2000.
[0109] 12 g (0.4% of the mass of the calcium carbonate coarse powder) of the above-mentioned grinding aid was sprayed on 3 kg of 400-mesh calcium carbonate coarse powder, poured into a 1580×800×1000 mm ball mill filled with 1.61 kg of water, and ground for 40 min to prepare a calcium carbonate slurry with a concentration of 65%.
[0110] Example 2
[0111] 300 g of wastewater from the production of acrylic acid and its esters, 50 g of sodium dodecylbenzene sulfonate and 27 g of allyl polyether with a molecular weight of 900 were stirred in a water bath at 45° C. for 1 hour to prepare a grinding aid.
[0112] Among them, the solid content of the above-mentioned acrylic acid and its ester production wastewater is 31.12%, the mass content of sodium acrylate is 16.38%, the mass content of sodium hydroxide is 11.78%, and the mass content of sodium p-toluenesulfonate is 2.96%; the model of sodium dodecylbenzene sulfonate is LAS-30; and the model of allyl polyether is APEG-900.
[0113] 12 g (0.4% of the mass of the calcium carbonate coarse powder) of the above-mentioned grinding aid was sprayed on 3 kg of 400-mesh calcium carbonate coarse powder, poured into a 1580×800×1000 mm ball mill filled with 1.61 kg of water, and ground for 40 min to prepare a calcium carbonate slurry with a concentration of 65%.
[0114] Example 3
[0115] 300 g of wastewater from the production of acrylic acid and its esters, 50 g of sodium dodecylbenzene sulfonate and 22 g of allyl polyether with a molecular weight of 1000 were stirred in a water bath at 45° C. for 1 hour to prepare a grinding aid.
[0116] Among them, the solid content of the above-mentioned acrylic acid and its ester production wastewater is 34.5%, the mass content of sodium acrylate is 17.95%, the mass content of sodium hydroxide is 12.45%, and the mass content of sodium p-toluenesulfonate is 4.1%; the model of sodium dodecylbenzenesulfonate is LAS-30; and the model of allyl polyether is APEG-1000.
[0117] 12 g (0.4% of the mass of the calcium carbonate coarse powder) of the above-mentioned grinding aid was sprayed on 3 kg of 400-mesh calcium carbonate coarse powder, poured into a 1580×800×1000 mm ball mill filled with 1.61 kg of water, and ground for 40 min to prepare a calcium carbonate slurry with a concentration of 65%.
[0118] Example 4
[0119] Example 4 is basically the same as Example 1, except that an equal mass of sodium lignin sulfonate is used to replace LAS-30, and an equal mass of alkylphenol polyoxyethylene ether is used to replace allyl polyether.
[0120] The sodium lignin sulfonate is in the form of a 30% mass concentration solution, and the alkylphenol polyoxyethylene ether is in the form of a 70% mass concentration OP-10 solution.
[0121] Example 5
[0122] Example 5 is substantially the same as Example 1, except that an equal mass of fatty alcohol polyoxyethylene ether is used to replace the allyl polyether.
[0123] Among them, the model of the above-mentioned fatty alcohol polyoxyethylene ether is AEO-9 with a mass concentration of 92%.
[0124] Example 6
[0125] Example 6 is substantially the same as Example 1, except that an equal mass of nonylphenol polyoxyethylene ether is used to replace allyl polyether.
[0126] The model of the nonylphenol polyoxyethylene ether is NP-10 with a mass concentration of 92%.
[0127] Example 7
[0128] Example 7 is substantially the same as Example 1, except that an equal mass of sodium dodecylbenzene sulfonate is used to replace the allyl polyether.
[0129] Comparative Example 1
[0130] Comparative Example 1 is substantially the same as Example 1, except that no grinding aid is added.
[0131] Comparative Example 2
[0132] Comparative Example 2 is basically the same as Example 1, except that the grinding aid does not contain the surfactant sodium dodecylbenzene sulfonate and allyl polyether, and the surfactant in the grinding aid is replaced by an equal mass of acrylic acid and its ester production wastewater.
[0133] Comparative Example 3
[0134] Comparative Example 3 is basically the same as Example 1, except that the wastewater produced by the production of acrylic acid and its ester in the grinding aid is replaced by an equal mass of sodium acrylate solution with a mass concentration of 30%.
[0135] Comparative Example 4
[0136] Comparative Example 4 is substantially the same as Example 1, except that sodium stearate is used in place of sodium dodecylbenzene sulfonate and allyl polyether in equal amounts.
[0137] The calcium carbonate slurries of Examples 1 to 7 and Comparative Examples 1 to 4 were tested for particle size distribution, viscosity, stability, oil absorption and activation, and the test results are shown in Table 1 below.
[0138] Among them, the test conditions or test standards for each performance test item are:
[0139] Particle size distribution: The calcium carbonate slurry was dried at 105°C for 8 h to obtain a powder, and the particle size distribution of the powder was tested using a laser particle size analyzer.
[0140] Viscosity test: Use a rotational viscometer to test the viscosity data of calcium carbonate slurry.
[0141] Stability test: Weigh 500 g of the above calcium carbonate slurry and place it in a beaker. Let it stand for 5 days to observe whether there is water precipitation or stratification.
[0142] Oil absorption test: The calcium carbonate slurry was dried at 105°C for 8 hours to obtain powder, and then the oil absorption value of the powder was tested according to GB / T 19281-2014.
[0143] Determination of activation degree: The calcium carbonate slurry was dried at 105°C for 8 h to obtain a powder, and then the activation degree of the powder was tested according to GB / T 19281-2014.
[0144] Table 1
[0145]
[0146] As can be seen from Table 1 above, the grinding aids obtained in Examples 1 to 7 significantly reduce the D50 in the calcium carbonate slurry, increase the content of particles below 2 μm, and improve the fluidity, stability, oil absorption and activation of the calcium carbonate slurry, making the calcium carbonate slurry have better performance. When the comparative example 1 does not use a grinding aid, the slurry is severely stratified and has poor stability. The direct use of acrylic acid and its ester production wastewater as a grinding aid in comparative example 2 has a certain positive effect on the particle grading, but the calcium carbonate slurry is slightly stratified, and the stability and activation need to be improved. In comparative example 3, the auxiliary effect of replacing wastewater with sodium acrylate aqueous solution is slightly better than that of directly using wastewater as a grinding aid, but the stability, activation and other properties are not significantly improved. The surfactant in comparative example 4 is replaced with sodium stearate, and the performance is not outstanding.
[0147] It can be seen from Examples 1 to 3 that the grinding aid includes wastewater from the production of acrylic acid and its esters, the sodium dodecylbenzene sulfonate and the allyl polyether, and when the mass ratio of the wastewater from the production of acrylic acid and its esters, the sodium dodecylbenzene sulfonate and the allyl polyether is 1:0.1-0.32:0.04-0.1, the wastewater from the production of acrylic acid and its esters, the sodium dodecylbenzene sulfonate and the allyl polyether interact with each other and synergize to further optimize the gradation and comprehensive performance of the calcium carbonate slurry. When the mass ratio of the wastewater from the production of acrylic acid and its esters, the sodium dodecylbenzene sulfonate and the allyl polyether is 1:0.15-0.25:0.06-0.08, the gradation and comprehensive performance of the calcium carbonate slurry are more prominent.
[0148] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0149] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A grinding aid, characterized in that: The grinding aid comprises a solution to be treated and a surfactant; the solution to be treated contains sodium acrylate, sodium hydroxide and sodium p-toluene sulfonate; the surfactant comprises at least one of sodium dodecylbenzene sulfonate, sodium lignin sulfonate, allyl polyether, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and nonylphenol polyoxyethylene ether.
2. The grinding aid according to claim 1, characterized in that The mass ratio of the solution to be treated to the surfactant is 1:0.08-0.
39.
3. The grinding aid according to claim 1, characterized in that At least one of the following conditions is met: (1) The surfactant includes sodium dodecylbenzene sulfonate and allyl polyether; (2) The surfactant includes the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether.
4. The grinding aid as claimed in claim 3, characterized in that At least one of the following conditions is met: (1) The mass ratio of the solution to be treated, the sodium dodecylbenzene sulfonate and the allyl polyether is 1:0.1-0.32:0.04-0.1; (2) The mass ratio of the solution to be treated, the sodium lignin sulfonate and the alkylphenol polyoxyethylene ether is 1:0.12-0.33:0.025-0.
08.
5. A grinding aid as described in any one of claims 1 to 4, characterized in that, The solution to be treated is wastewater from the production of acrylic acid and its esters, the solid content of the wastewater from the production of acrylic acid and its esters is 30% to 50%, the mass content of the sodium acrylate in the wastewater from the production of acrylic acid and its esters is 15% to 37%, the mass content of the sodium hydroxide in the wastewater from the production of acrylic acid and its esters is 0.3% to 13%, and the mass content of the sodium p-toluenesulfonate in the wastewater from the production of acrylic acid and its esters is 0.3% to 5%.
6. A method for preparing a grinding aid as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: blending the solution to be treated and the surfactant to prepare the grinding aid.
7. The method for preparing a grinding aid as claimed in claim 6, wherein: At least one of the following conditions is met: (1) The solution to be treated is wastewater produced by the production of acrylic acid and its esters, and before the blending, it also includes a concentration step: based on the mass content, the wastewater produced by the production of acrylic acid and its esters with a solid content of 2% to 20% is concentrated into the wastewater produced by the production of acrylic acid and its esters with a solid content of 30% to 50%; (2) The blending temperature of the blending is 40°C to 50°C.
8. Use of the grinding aid according to any one of claims 1 to 5 in a grinding process.
9. A use according to claim 8, characterized in that The steps include: The calcium carbonate coarse powder is wet-ground with the grinding aid and water to prepare calcium carbonate slurry.
10. The use according to claim 9, characterized in that At least one of the following conditions is met: (1) The amount of the grinding aid added is 0.2% to 0.5% of the mass of the calcium carbonate coarse powder; (2) The average particle size of the calcium carbonate coarse powder is 250 mesh to 500 mesh; (3) The grinding time of the wet grinding is 25min~45min.
Citation Information
Patent Citations
Automotive glass decontaminant and preparation method thereof
CN107118866A
Special grinding aid for calcium carbonate powder and use method of special grinding aid
CN111808438A
Cement grinding aid and application thereof
CN115057637A
High-dispersity calcium powder and preparation method thereof
CN117447856A